Letter to Jane Tolmach from Joyce Fadem - Joyce Fadem:::::: (1967)
A memo from Joyce Fadem that invites Jane Tolmach to attend a planning meeting with State Chairman Charles Warren and other Southern California organizers for the January Campaign Launching Conference. The meeting is scheduled for November 5, 1967, in Los Angeles and will focus on progress reports, unresolved issues, and remaining tasks related to the conference. The memo stresses that her attendance is needed and strongly encouraged.